Case–Control Investigation of Association of Clinician‐Determined Variables With Progressive Myelomalacia After Acute Thoracolumbar Disc Extrusion in Dogs - Eileen Donoghue; Joe Mankin; Nick Jeffery (Journal of Veterinary Internal Medicine, 2025)
ABSTRACT Background Reliable identification of clinician‐controlled factors that increase the risk of progressive myelomalacia after acute thoracolumbar intervertebral disc extrusion could aid in decreasing its occurrence. Hypothesis/Objectives Examination of possible risk factors for the development of progressive myelomalacia in a susceptible sample population of adequate size to achieve sufficient power to re‐evaluate previously reported associations. Animals A total of 244 dogs with acute thoracolumbar intervertebral disc extrusion presented to a single neurology clinic with absent pain perception in the hindquarters. Methods Case–control study analyzing the association of exposure to putative risk factors with the development of progressive myelomalacia within 14 days of decompressive surgery. Results Progressive myelomalacia was not associated with any of the clinician‐controlled factors examined, including surgical timing and duration, peri‐operative anti‐inflammatory medications, or variations in intra‐operative blood pressure. Some evidence supported previous associations of progressive myelomalacia with disc extrusion in the lumbar intumescence and with French bulldog breed, but study power was insufficient to confirm these associations. Unneutered dogs, notably males, had increased incidence in this sample, but this finding might be unreliable because of unknown, likely low, study power. Conclusions and Clinical Importance Progressive myelomalacia was not associated with factors that can be controlled by clinicians and that were investigated in our study. It will be necessary to develop new therapeutic approaches to decrease the occurrence of progressive myelomalacia. The possibility that unneutered dogs are at higher risk requires repeated investigation in another sample population.